Design and implementation of artificial hand for handicapped - Muhammed, S. Salim; Zainab, Ibraheem; M., Nsaif (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Arau, Perlis, Malaysia.